A retrospective study demonstrating the growth patterns and the pseudoprogression temporal classification after stereotactic radiosurgery for sporadic vestibular schwannomas - Amr M N El-Shehaby; Wael A Reda; Khaled M Abdel Karim; Ahmed M Nabeel; Reem M Emad Eldin; Ahmed H Alazzazi; Sameh R Tawadros (Scientific Reports)
Abstract Background and objectives Vestibular schwannomas are known to demonstrate tumor expansion, commonly referred to as pseudoprogression, after SRS. It is critical to differentiate between true tumor progression and pseudoprogression as this may entail performing an unnecessary intervention, such as surgery or repeat radiosurgery. This study aims to identify the fate of tumor enlargement that may occur after SRS for vestibular schwannomas and to propose a management algorithm for vestibular schwannoma enlargement after SRS. Methods In this retrospective study, we included 171 patients with sporadic vestibular schwannomas who showed tumor enlargement after SRS. The mean dose was 11.9 Gy (10–12 Gy). The mean tumor volume was 4.1 cc (0.1–19.7 cc). More than half of the tumors were Koos grade 4 (Koos 1: 8 (5%), 2: 20 (12%), 3: 43 (25%), 4: 100 (58%)). Volumetric changes and clinical outcomes were recorded. Different progression patterns were recorded according to the tumor volume changes (TVC) and the timings of TVC. Results The pseudoprogression rate among the patients who showed tumor enlargement after SRS was 83% (142/171). The mean follow-up duration was 64 months (12–241 months). The actuarial progression-free survival at 5-,7- and 10-years was 95%, 92%, and 90%, respectively. The mean follow-up duration was 64 months (12–241 months). The mean TVC at progression (TVCp) was 72% (11–439%). The mean time to tumor progression was 13 months (2–160 months) and the mean duration of TVC was 15 months (2–164 months). Late pseudoprogression (after 3 years) occurred in 30 patients (21%). In early PP, there was a shorter duration of volume change, and a presence of CLC. In true progression, there was a bigger TVCp, a bigger TVCf and a bigger tumor volume at the final follow-up (TVf). Clinical decline was observed with tumor enlargement in 36% of the patients, but in most of them, improvement occurred without the need for tumor intervention. Conclusion GKR for VS is associated with radiation-induced tumor enlargement in a group of patients. Pseudoprogression may occur beyond 5 years after treatment. A more conservative approach may be adopted in most vestibular schwannomas that exhibit tumor enlargement after SRS, as in most cases, they will eventually be controlled.